River proximity and urban park attributes influence bird diversity in Arequipa, Peru - MARIA RIVERO-MAMANI; LUIS VILLEGAS-PAREDES; JOSE VILLASANTE-BENAVIDES; CESAR R. LUQUE-FERNANDEZ (Society for Indonesian Biodiversity, 2025)
Abstract. Rivero-Mamani M, Villegas-Paredes L, Villasante-Benavides J, Luque-Fernandez CR. 2025. River proximity and urban park attributes influence bird diversity in Arequipa, Peru. Biodiversitas 26: 5838-5847. Urban green spaces are critical for sustaining biodiversity in rapidly expanding cities, yet their ecological function in arid landscapes remains poorly understood. This study examines how park attributes and river proximity influence bird diversity across 12 urban parks in Arequipa, southern Peru. Bird surveys were conducted using standardized point counts from January to June 2020. For each park, habitat structure, vegetation cover, noise level, and distance to the Chili River were quantified, and their effects on species richness and abundance were evaluated using model selection based on Akaike's Information Criterion. A total of 28 species were recorded in the urban parks, with Passeriformes and Columbiformes being well represented. The most frequent and abundant species were Turdus chiguanco and Zenaida meloda. Variation in species richness and abundance showed significant differences among the parks and sampling months. Parks located closer to the river exhibited higher diversity during the study period. In the analysis of structural characteristics and bird diversity, the models indicated that although distance to the river was not a relevant predictor, bird richness responded significantly to certain attributes, such as the proportion of green area, park size, and distance to the nearest agricultural zone. In contrast, abundance and Shannon-Wiener diversity did not show significant responses. These findings underscore the ecological importance of riparian connectivity and vegetation structure in enhancing avian diversity within arid urban settings. Integrating green space design with river corridor conservation could improve habitat quality, strengthen urban ecological networks, and support long-term biodiversity resilience in Andean cities.